The Effect of Service Quality and Product on Loyalty through Imagery and Customer Satisfaction Alfa Mart Jungke Karanganyar - Handayani, Wiwik (-)
This study aims to determine empirically and analyze the effect of quality of service and product loyalty through image and customer satisfaction Alfa Mart Jungke Karanganyar. Techniques of analysis in this research is the analysis of multiple linear regression lines, validity and reliability, linearity test and test hypotheses that include multiple linear regression, simultaneous test (F test), partial test (t test), determination coefficient and path analysis.T Test Results: In the first equation can be concluded that the variable quality of service and products significantly influence the image. In the second equation can be concluded that the variable quality of service and products significantly influence satisfaction. In the third equation can be concluded that the quality of services, products, and satisfaction Significant effect on loyalty. While the image of the variables not significant effect on loyalty. F test can be concluded jointly variable quality of service, product, image and satisfaction significantly influence consumer loyalty Alfa Mart Jungke Karanganyar. R2 can be concluded that the total value of R2 can be interpreted totaling 0.977 variation in Alfa Mart Consumer Loyalty Jungke Karanganyar explained by the variable quality of service, product, image and satisfaction of 97.7% and the remaining 2.3% described other variables outside the model study.Quality of service to the loyalty of more effective use of lanes indirectly, ie through varaibel satisfaction. product loyalty more effectively use the direct path without passing through the image and satisfaction as a result of the direct effect is greater than the indirect effectKeywords: quality of services, products, citra, satisfaction, loyalty